Venus Kinase Receptors at the Crossroads of Insulin Signaling: Their Role in Reproduction for Helminths and Insects - Dissous, Colette (Frontiers in Endocrinology, 2015)
Venus kinase receptors (VKRs) are invertebrate receptor tyrosine kinases (RTKs) first discovered in the human parasite Schistosoma. They contain an extracellular Venus FlyTrap (VFT) module similar to the ligand-binding domain of G protein-coupled receptors of class C and an intracellular tyrosine kinase domain similar to that of insulin receptors. VKRs are present from cnidarians to echinoderms. They were shown to be activated by amino-acids, to induce insulin-like intracellular pathways and to be highly expressed in larvae and in gonads of helminths and insects. The function of VKR in gametogenesis was demonstrated in schistosomes by VKR silencing and recent studies in Aedes aegypti have confirmed the importance of VKR in mosquito egg formation. AaeVKR was shown to bind to ovary ecdysteroidogenic hormone (OEH) and to activate the production of ecdysteroids by the ovary, independently of signaling mediated by insulin-like peptides. These new data confirm and specify the function of VKRs in the reproduction of helminths and insects and they open interesting perspectives for elucidating the role of VKRs in other models. VKR targeting would also provide opportunities for the control of parasites and various vector-borne diseases.